An other way to define the trigonometric functions is by using their power series, that is: $$ \sin x = \sum_{n=0}^{\infty}\frac{(-1)^n x^{2n+1}}{\left ( 2n+1 \right )!},\; \cos x = \sum_{n=0}^{\infty}\frac{(-1)^n x^{2n}}{\left ( 2n \right )!}, \; x \in \mathbb{R} $$ The classic definition of the trigonometric functions is based on the unit circle.

**a.** Use the definition given above to prove that:

- \( \sin 0 =0, \; \cos 0 =1 \)
- \( \left ( \sin x \right )'= \cos x , \; \left ( \cos x \right )' =-\sin x \)
- \( \sin^2 x + \cos^2 x =1 \)

**b. ** Prove that the classic definition, the definition given above and the definition \( \displaystyle \sin x = \frac{e^{ix}-e^{-ix}}{2i}, \; \cos x =\frac{e^{ix}+e^{-ix}}{2} \) are equivalent.